(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Human rights, right that belong to an individual or group of individuals simply for being human, or as a consequence of inherent human vulnerability, or because they are requisite to the possibility of a just society. Whatever their theoretical justification, human rights refer to a wide continuum of values or capabilities thought to enhance human agency or protect human interests and declared to be universal in character, in some sense equally claimed for all human beings, present and future. t is a common observation that human beings everywhere require the realization of diverse values or capabilities to ensure their individual and collective well-being. It also is a common observation that this requirement whether conceived or expressed as a moral or a legal demand is often painfully frustrated by social as well as natural forces, resulting in exploitation, oppression, persecution, and other forms of deprivation. Deeply rooted in these twin observations are the beginnings of what today are called “human rights and the national and international legal processes associated with them.